Resveratrol Induces Differentiation of Human Umbilical Cord Mesenchymal Stem Cells into Neuron-Like Cells - Li Guo; Liang Wang; Li Wang; Shi Yun-peng; Jing-jing Zhou; Zongmao Zhao; De-Pei Li (Stem Cells International)
Objective. Human umbilical cord mesenchymal stem cells (hUC-MSCs) potentially differentiate to various types of cells including neuron-like cells. The natural polyphenol resveratrol benefits patients with many diseases including ischemic brain injury. We hypothesize that resveratrol induces differentiation of hUC-MSCs into neuron-like cells. Methods. Flow cytometry was used to determine the surface antigens in different stage of hUC-MSCs (P2, P5, and P10). Nestin, neuron-specific enolase (NSE), and glial fibrillary acidic protein (GFAP) were detected by immunocytochemistry, Western blotting, and real time RT-PCT. The cultured hUC-MSCs were treated with resveratrol at different concentrations (0, 7.5, 15.0, and 30.0 mg/L). Nestin, GFAP, and NSE protein and mRNA were measured at posttreatment time points of 2 h, 4 h, 6 h, 12 h, and 24 h. Results. Neuron-like cells were found in hUC-MSCs treated by resveratrol at concentrations of 15.0 and 30.0 mg/L, but not in hUC-MSCs treated with vehicle and 7.5 mg/L resveratrol. Furthermore, immunocytochemical staining revealed that nestin and NSE immunoreactivities were positive in resveratrol-treated hUC-MSCs at concentrations of 15.0 and 30.0 mg/L. Resveratrol treatment significantly increased nestin and NSE protein and mRNA levels 4 h after the treatment. However, resveratrol treatment did not change GFAP immunoreactivities and protein and mRNA expression levels in cultured hUC-MSCs. Conclusions. Taken together, resveratrol treatment induces a differentiation of hUC-MSCs into neuron-like cells at relatively high concentrations.